A New Species of Abbrosoga (Hemiptera: Fulgoroidea: Delphacidae), An Endemic Puerto Rican Planthopper Genus, with an Updated Checklist of the Delphacidae of Puerto Rico - Otero, Miriel; Bartlett, Charles R. (Zootaxa, 2019)
The genus Abbrosoga Caldwell (Delphacidae: Delphacinae: Delphacini) was described in Caldwell & Martorell (1951) to include the single species Abbrosoga errata Caldwell, 1951. Here, a second species, Abbrosoga multispinosa n. sp. is described. Revised diagnostics are presented for the genus and A. errata, including a key to species. A compiled list of 64 delphacid species from Puerto Rico is presented, with updated nomenclature, including the new species and a new record of Delphacodes aterrima for Puerto Rico.